Analysis of the Effect of Temperature, Lighting and Noise on Employee Work Productivity in the Noodle Production Section at CV. Kartika Makassar - Yan Herdianzah; A Dwi Wahyuni P; Rahmaniah Malik; Muhammad Aqsan Pratama (PT. SAFARI AMALIA, 2023)
A comfortable work environment is needed by humans to be able to carry out activities optimally and productively. Therefore the work environment must be handled and designed properly. A good temperature in the workplace will support the activities carried out by workers by meeting predetermined standards.. The objectives to be achieved in this study are to find out how much influence temperature / temperature, noise and lighting in the work environment have on employee work productivity in the noodle production section at CV. Kartika Makasar. This research will be conducted at CV. Kartika Makassar, which is located at Jalan Setia 1 Blok AB No. 4 Ex. Buntusu Kec. Tamalanrea Makassar City, South Sulawesi Province. In the analytical method where data processing uses the Classical Assumption Test in the form of a Linear Regression Test which is used to determine the direction and how much influence the independent variables have on the dependent variable. Based on the results of the analysis and discussion, it shows that in the physical work environment, namely temperature (X1) with a value of 0.560 > 0.05 and lighting (X2) 0.516 > 0.05 indicates that the hypothesis is rejected. Thus the temperature and lighting at CV Kartika Makassar are good because together they do not affect the work productivity of employees or operators. As for Noise (X3) 0.034 <0.05, indicating that the hypothesis is accepted thus it has a significant effect on the work productivity of employees or operators.